Demographics and clinical characteristics of a new population of centenarians in Colombia. The COOLCEN cohort - Ivan David Lozada-Martinez; Juan Sebastian Marín; Sandra Milena Castelblanco-Toro; Enrique A Mazenett-Granados; John Fredy Suárez; Mauricio Sarmiento; Juan-Manuel Anaya (Archives of Gerontology and Geriatrics Plus)
Aim: Centenarians represent a successful model of biological aging that is becoming increasingly common but still largely unknown. Data about centenarians in Colombia is scarce. The aim of this study was to provide a description of the demographic and clinical characteristics of a new cohort of centenarians in Colombia. Methods: A retrospective, population-based cohort study was undertaken, employing a nationally validated registry provided by a health insurance company. Demographic information and prevalence rates of significant chronic diseases were evaluated. The geographical distribution of centenarians at the national level was mapped. Data were then compared with other age groups (>18-59 and 60-99 years-old), and with previous descriptions of centenarians. Results: Among the 2,362,436 persons included in the study, a prevalence of 0.12% centenarians was observed, of which 50.7% were female and the majority resides in urban areas (64.9%). Chronic diseases were observed in 275 (9.27%) centenarians, of whom 113 (3.81%) disclosed one chronic disease and 162 (5.46%) disclosed multimorbidity. The most prevalent chronic diseases were essential hypertension (8.6%), and chronic kidney disease (4.4%), which were significantly lower compared to others age groups. Centenarians were free of hematological, inflammatory arthritis, tuberculosis and human immunodeficiency virus infections. COVID-19 was observed in 2% of cases. Significant differences in health outcomes assessed were seen when comparing our results with centenarians from previously described blue zones. Conclusions: The COOLCEN cohort discloses a low prevalence of age-related chronic diseases, low economic status and no difference in gender distribution. The study will provide valuable insights into healthy aging, disease prevention, and improving the well-being of older adults.